The Effect of Oxytocics on the "Ca-Deficient" Uterus : A measure of oxytocic potency - Coutinho, Elsimar M. (The Rockefeller University Press, 1959)
If the excised, parturient rabbit uterus is repeatedly treated with a Krebs solution free from Ca, its tension in a tetanus drops gradually, and in 15 to 30 minutes becomes zero. We call such a uterus "Ca-deficient." The uterus in this condition has a high threshold, it is non-propagating, "inexcitable," fails to respond to oxytocics in a characteristic fashion, but retains maximum contractility. As Ca is gradually restored to the Krebs, these lost qualities return in a graded fashion and tension of the tetanized uterus becomes a log function of the [Ca]. If the [Ca] is kept low, i.e. 1/10 to 1/20 of the normal, tetanic tension is small but steady, and the preparation offers a full scale of tension increment for the measurement of oxytocic potency. Keeping the stimulus and the [Ca] constant, excitability (measured by tension increment) is a log function of the drug concentration. The recovery of excitability by restoring Ca to the Ca-deficient uterus is strongly temperature-dependent. The Ca-deficient uterus is a useful preparation for the study of the mechanism of regulation. When its excitability is partially recovered by Ca, the electrically stimulated uterus becomes an excellent tool for the quantitative measurement of oxytocic potency.